Impact of molecular order on polaron formation in conjugated polymers - Nightingale,J; Wade,J; Moia,D; Nelson,J; Kim,J-S (The Journal of Physical Chemistry C, 2018)
The nature of polaron formation has profound implications on the transport of charge carriers in conjugated polymers, but still remains poorly understood. Here we develop in situ electrochemical resonant Raman spectroscopy, a powerful structural probe that allows direct observation of polaron formation. We report that polaron formation in ordered poly(3-hexyl)thiophene (P3HT) polymer domains (crystalline phase) results in less pronounced changes in molecular conformation, indicating smaller lattice relaxation, compared to polarons generated in disordered polymer domains (amorphous phase) for which we observe large molecular conformational changes. These conformational changes are directly related to the effective conjugation length of the polymer. Furthermore, we elucidate how blending the P3HT polymer with phenyl C-61 butyric acid methyl ester (PCBM) affects polaron formation in the polymer. We find that blending disturbs polymer crystallinity, reducing the density of polarons that can form upon charge injection at the same potential, whilst the lost capacity is partly restored during post-deposition thermal annealing. Our study provides direct spectroscopic evidence for a lower degree of lattice reorganisation in crystalline (and therefore more planarised) polymers than in conformationally disordered polymers. This observation is consistent with higher charge carrier mobility and better device performance commonly found in crystalline polymer materials.